A religião manifesta enquanto lugar da tomada de consciência-de-si do espírito como espírito na Fenomenologia do Espírito de Hegel - Fieni, Vitor Hugo de Oliveira (2010)
In his first important work, Phenomenology of Spirit (1807), Hegel had already put forward the reasons why religion was so highly considered by him. The religious phenomenon was thought out by that philosopher as an event through which the spirit (Geist) gradually reaches self-knowledge as spirit. This occurs insofar as the religious consciousness has as its object an Other which is itself. Yet, this equality is not clear to that consciousness at the outset of its journey towards Absolute Knowledge. Its process of identification with itself will be translated into a gradual essentialization of immanence and immanentization of the essence, and this occurs in all religions presented by Hegel. In this work, I carry out an analysis of manifest religion (offenbare Religion) as dealt with by that philosopher, while I also analyze moments such as the locus where the spirit´s knowledge of itself occurs fully, insofar as God becomes human and the humans become God. Yet, considering that such synthesis does not happen instantly, I pursue in this work the dialectic thread which leads to the deification of the humans and the humanization of God by way of natural religion and art religion, until we reach the figure of Christ, which is the perfect synthesis of God and the humankind. The death of the Messiah and the development of the Christian Community are the final touch to this spirit which becomes self-conscious of itself, from itself, since, through the sacrifice of the Son of God, his Self oneness is universally extended to those individual members of the Community who, thanks to the (Holy) Spirit, enter into communion with the eternal essence. However, religion is not the last chapter in Phenomenology, as, for Hegel, the synthesis, identity and knowledge-of-itself of the spirit as spirit emerges in manifest religion by means of representation (Vorstellung). Thus, a reconciliation was needed that could be more intelligible and less sensitive: the absolute philosophical knowledge. In other words, human deification, side by side with divine anthropomorphization, religiously achieved, were not sufficient to enable consciouness to reach its final stage. In view of this, I undertake a final critical chapter, to approach the humanistic consequences of hegelian philosophy. In this chapter, I also discuss Hegel´s position in relation to what he calls God (Gott). In conclusion, I suggest the concept of hegelian anthropo-pantheism as the result of Hegel´s Absolute Knowledge.